Cardiovascular risk factors in climacteric women with hyperuricemia - N. V. Tagiltseva; N. V. Izmozherova; A. A. Popov; A. N. Andreev (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study risk factors (RF) of cardiovascular disease (CVD) in climacteric women with hyperuricemia. Material and methods. This cross-sectional study included 672 women, divided into quartiles (n=168 each) by uric acid (UA) levels. Patients from 1st and 4th quartiles were compared. Anthropometry, lipid and carbohydrate metabolism parameters were assessed, arterial hypertension (AH), coronary heart disease, and chronic heart failure were diagnosed. Stroke, transient ischemic attack, and myocardial infarction in anamnesis were also registered. Results. Hyperuricemia was observed in 190 women. In 4th quartile, obesity and overweight prevalence was significantly higher than in 1st quartile: 62 (36,9%), 69 (41,1%) and 43 (25,6%), 63 (37,5%), respectively. More than 50% of the 4th quartile patients had waist circumference >88 cm. In hyperuremic women, hypertriglyceridemia, low levels of high-density lipoprotein cholesterol (HDL-CH), plus increased levels of very low-density lipoprotein cholesterol (VLDL-CH) and atherogenicity index (AI) were significantly more prevalent. Conclusion. In climacteric women with hyperuricemia, abdominal obesity and hypertriglyceridemia prevalence, VLDL-CH and AI levels are increased, and HDL-CH levels are decreased.